Does the placement of acetabular cups differ between right and left sides for a right-handed surgeon operating through a direct lateral approach? A comparative study - Ahmed A. Khalifa; Ahmed M. Abdelaal (Arthroplasty)
Abstract Purpose Although many factors were suggested to affect acetabular cup positioning during primary total hip arthroplasty, the effect of surgeon handedness was rarely evaluated. We aimed primarily to assess the difference in cup positioning (inclination and anteversion) between the right and left sides during primary THA. Secondly, to check the difference in the percentages of cups positioned in the safe zone for inclination and anteversion and if there will be a difference in cup positioning according to the type of cup fixation (cemented vs. cementless). Methods Cup inclination and anteversion of 420 THAs were radiographically evaluated retrospectively. THAs were performed by a senior right-handed surgeon, who operated through a direct lateral approach in a lateral decubitus position using manual instruments and freehand technique for cup placement. Patients were assigned to two groups: Group A (right, or dominant side), and Group B (left, or non-dominant side), with equal cases of THAs (n = 210) in each group. Results No difference was found in patients’ basic characteristics, preoperative diagnosis, and cup fixation (54.3% cemented and 45.7% cementless) between the two groups. There was a significant difference in cup inclination between Groups A and Group B (40.1° ± 6.3° vs. 38.2° ± 6.1°) (P = 0.002). No significant difference was revealed in anteversion between the two groups (11.7° ± 4.4° vs. 11.8° ± 4.7°) (P = 0.95). The percentage of cups located within the safe zone in terms of both inclination and anteversion was 85.2% vs. 83.8% and 69% vs. 73.3% for Group A and Group B, according to Lewinnek and Callahan’s safe zones, respectively. There existed a significant difference in the cemented cup inclination between Group A and Group B (40.8° ± 6.4° vs. 38.3° ± 6.3°) (P = 0.004). Conclusion Cup inclination is affected by the surgeon’s handedness when operating through a direct lateral approach and using a freehand technique, while anteversion is less affected. Furthermore, the difference is greater with cemented cups.